What Makes Imprisonment More Painful? A Study from the Perspective of the COVID-19 Pandemic - Friedrich, Wiola; Krasińska, Magdalena (Deviant behavior, 2023)
We compared stress of imprisonment and stress coping styles of incarcerated people before and during COVID-19. We aimed to explore how the sanitary conditions of COVID-19 affected the well-being of incarcerated people. The aim of the study was to distinguish predictors of well-being in incarcerated people as a function of stress assessment, coping styles and COVID-19 restrictions, compensation and prison preparation. In total, we surveyed 239 incarcerated people during the third wave of the pandemic from December 2021 to February 2022 and 247 subjects before the COVID-19 pandemic. The study results showed that the pandemic had adverse effects on incarcerated people. We found differences between groups in perceived stress and some stress coping styles. Among psychological stress traits, harm-loss and emotion-oriented stress coping could be the predictors of well-being among incarcerated people as well as COVID-19 restrictions implemented in prisons, including high-security facilities. The implications for prison policy and practice were also discussed.